2019
DOI: 10.3390/nu11050973
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Breakfast Frequency and Cardiovascular Disease (CVD) Risk Factors among Adolescents in Malaysia

Abstract: Breakfast frequency is associated with cardiovascular disease (CVD) risk in Western populations, possibly via the types of food eaten or the timing of food consumption, but associations in Malaysian adolescents are unknown. While the timing of breakfast is similar, the type of food consumed at breakfast in Malaysia differs from Western diets, which allows novel insight into the mechanisms underlying breakfast–CVD risk associations. We investigated foods eaten for breakfast and associations between breakfast fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…Results from the WHO Health Behavior in School-Aged Children survey in Belgium are in line with previous findings which showed that eating culture plays a role in inequalities of eating habits among immigrants when socioeconomic conditions are considered [26]. Mustafa N. et al [27] further highlighted that the type of foods consumed at breakfast are highly dependent on culture. Malaysian adolescents consume breakfast that is of low nutrient quality, such as cereal-based and often primarily rice dishes, chocolate and confectionary, hot and powered drinks, and noodles.…”
supporting
confidence: 86%
“…Results from the WHO Health Behavior in School-Aged Children survey in Belgium are in line with previous findings which showed that eating culture plays a role in inequalities of eating habits among immigrants when socioeconomic conditions are considered [26]. Mustafa N. et al [27] further highlighted that the type of foods consumed at breakfast are highly dependent on culture. Malaysian adolescents consume breakfast that is of low nutrient quality, such as cereal-based and often primarily rice dishes, chocolate and confectionary, hot and powered drinks, and noodles.…”
supporting
confidence: 86%
“…Marchioni et al [21] evaluated 795 adolescents in São Paulo/Brazil and found that 38% skipped breakfast. Eating breakfast is hypothesized to reduce subsequent snack consumption, resulting in lower overall daily energy intake, thus maintaining energy balance and a lower body weight, if it is not associated with higher energy product intake [38]. For low-income people, household food insecurity can limit access to adequate foods, which may lead to problems such as insufficient nutrients and food intake, leading to health issues such as chronic diseases, mental health problems, and poor quality of life [39].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of economic restrictions on the value of food leads to diets with low participation of fruits and vegetables and with high energy density [57,58]. breakfast composition can impact the body mass index and the risk of developing noncommunicable diseases [4,38]. The combination of whole cereals with dairy products plays a protecting role, while high-fat and processed foods, such as processed meat, cheese, and margarine, are associated with a higher risk of developing noncommunicable diseases [4].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the percentage of high school boys going to class without having had any breakfast at all increases from 8.2% at 11–12 years of age to 24.6% at 17–18 years of age [ 15 ]. Numerous studies point out that regular consumption of breakfast has also been associated with lower BMI [ 40 , 41 , 42 , 43 ]. Adherence to a weight loss diet can lead to skipping breakfast altogether or having an unhealthy breakfast, mainly as a result of wanting to stay in shape or lose weight, with this habit being more frequent amongst girls [ 44 ].…”
Section: Introductionmentioning
confidence: 99%